Kinetics of Protein Complex Dissociation Studied by Hydrogen/Deuterium Exchange and Mass Spectrometry - Zhang, Zhe (Anal Chem, 2015)
The growing importance of protein aggregation diseases requires the development of new methods to elucidate the molecular features that are responsible for the incipient protein-protein interactions. Kinetic information from protein-protein association/dissociation reactions is particularly valuable for revealing mechanistic insight, but robust tools that can provide this information are somewhat lacking. In this work, we describe a hydrogen/deuterium exchange (HDX)-based method that provides rate constant information for protein oligomer dissociation, using the well-studied β-lactoglobulin (βLG) dimer as a model system to validate our approach. By measuring the rate of exchange at different regions of the protein using top-down tandem mass spectrometry and fitting the resulting data to an appropriate mathematical model, we are able to extract the dimer’s dissociation rate constant. We exploit the fact that regions of the protein that are part of the protein-protein interface have exchange patterns that are distinct from non-interfacial regions. This observation indicates that the HDX/MS method not only provides kinetic information but could also provide structural insight about the interface at the same time, which would be very valuable for previously uncharacterized protein-protein complexes.